2022
DOI: 10.3390/catal12060585
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Oxygen Electrocatalysis by Combining Iron Nanoparticles with Single Atoms

Abstract: The development of high-performance non-noble metal-based oxygen electrocatalysts is crucial for the practical application of zinc–air batteries. Most of them suffer from low intrinsic activity and poor stability, failing to meet the needs of practical applications. Here, we report an efficient and durable bifunctional oxygen electrocatalyst of Fe@Fe-SAC composite (SAC stands for single atoms on carbon). A facile and ease-to-scale-up process synthesizes it. Fe single-atom and Fe nanoparticles are anchored on n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Additionally, a homogeneous dispersion of nanoparticles, as witnessed in the FE-SEM image of C/Fe.S.N, is possibly the reason for this high activity. The doping mechanism thus leads to improved activity (60-70 mV positively shifted onsets), better dispersion, as reported earlier [46,47], and smaller particles that can optimize ORR processes, which is in line with previous studies [48].…”
Section: Electrochemistrysupporting
confidence: 90%
“…Additionally, a homogeneous dispersion of nanoparticles, as witnessed in the FE-SEM image of C/Fe.S.N, is possibly the reason for this high activity. The doping mechanism thus leads to improved activity (60-70 mV positively shifted onsets), better dispersion, as reported earlier [46,47], and smaller particles that can optimize ORR processes, which is in line with previous studies [48].…”
Section: Electrochemistrysupporting
confidence: 90%
“…During the preparation process, conditions such as high temperatures tend to promote the formation of metal clusters. Liu et al [123] proposes a new possibility for the development of SACs: the single-atom sites do not need to be uniformly dispersed or maintained for a long time, and in time, the formation of nanoclusters can be synergized with a small number of singleatom sites to enhance the activity of the catalysts. Meanwhile, the design idea also solves the stability problem of SACs.…”
Section: Synergism Between Nanoparticles and Single Atommentioning
confidence: 99%
“…Liu et al. [ 123 ] synthesized Fe@Fe‐SAC composites by a simple two‐step method using sodium alginate as the carbon precursor. TEM images show well‐dispersed nanoparticles embedded in carbon fibers (≈7 nm).…”
Section: Structural Regulation Of Sacs For Oermentioning
confidence: 99%
See 1 more Smart Citation
“…[ 30 ‐– 33 ] Recently, it has been demonstrated that single metal atoms could synergy with metal nanoparticles to collaboratively improve the performance of electrocatalysts by modifying the electronic structure of metals. [ 34 ‐– 36 ] For example, Yang et al. investigated the synergistic effect of PtSA and CoPt nanoparticles for HER.…”
Section: Introductionmentioning
confidence: 99%